War Despatches: Operation Iraqi Freedom - Ashok K Mehta; MEHTA (Ashok K) (New Delhi Har Anand Publications Pvt Ltd, 2004)
Gives an account of America's on going war in Iraq. This book presents an Indian soldier's account and interpretation of the war. It also provides an overview of the three week long war.
Keywords: Middle East History; Iraqi Freedom; Weapons of Mass Destruction